Climate Change Adaptation in the Environment Court: Revisiting the 2010 Holt Case - Magallanes, CJ Iorns; Dicken, MJ (Victoria University of Wellington Law Review, 2019)
Common law precedents for some resource consent approvals in Aotearoa New Zealand are out of date due to the rapid increase in the science and understanding of the effects of climate change. This article considers one 2010 Environment Court case on a resource consent for building in the coastal area. It examines how the case would be decided if it arose today, with the benefit of the relevant law, policies and guidance now available to decision-makers. It suggests that the option taken by the Court in 2010, whereby the owners assumed the relevant inundation risks, would not be so available to a court today. This case is thus no longer good law.